Healthcare professional requirements for the care of adult diabetes patients managed with insulin pumps in Australia. Issue 1 (January 2015) - Xu, S.; Alexander, K.; Bryant, W.; Cohen, N.; Craig, M. E.; Forbes, M.; Fulcher, G.; Greenaway, T.; Harrison, N.; Holmes‐Walker, D. J.; Howard, G.; Jackson, J.; et al.
Abstract Background Healthcare professional (HCP) time supporting insulin pump therapy (IPT) has not been documented, yet it is important in planning and allocating resources for effective care. Aim This study aims to determine HCP time spent in IPT patient care to inform resource planning for optimal IPT delivery. Methods Twenty‐four Australian adult IPT‐experienced institutions (14 government funded, seven private, three both) collected data between April 2012 and January 2013 prospectively, including: patient demographics, HCP classification, purpose of HCP–patient interaction, interaction mode and HCP time with the patient. A subset of patients was tracked from pre‐pump education until stable on IPT. Results Data on 2577 HCP‐adult patient interactions (62% face‐to‐face, 29% remote, 9% administrative) were collected over 12.2 ± 6.4 weeks for 895 patients; age 35.4 ± 14.2 years; 67% female; 99% type 1 diabetes, representing 25% of all IPT patients of the institutions. Time (hours) spent on IPT interactions per centre per week were: nurses 5.4 ± 2.8, dietitians 0.4 ± 0.2 and doctors 1.0 ± 0.5. IPT starts accounted for 48% of IPT interaction time. The percentage of available diabetes clinic time spent on outpatient IPT interactions was 20.4%, 4.6% and 2.7% for nurses, dietitians and doctors respectively. Fifteen patients tracked from pre‐pump to stabilisation over 11.8 ± 4.5 weeks, required a median (range) of 9.2 (3.0–20.9), 2.4 (0.5–6.0) and 1.8 (0.5–5.4) hours per patient from nurses, dietitians and doctors respectively. Conclusions IPT patient care represents a substantial investment in HCP time, particularly for nurses. Funding models for IPT care need urgent review to ensure this now mainstream therapy integrates well into healthcare resources.